ANALYSIS OF COST CONTROL SYSTEM IMPLEMENTATION IN IMPROVING MICRO-ENTERPRISE EFFICIENCY (Case Study: Mrs. Delin’s Grocery Business in Tuni Hamlet) - Rita J D Atarwaman; Fioneti T Birahy; Fensya Penina; Muhammad Maulud Samal; Yehezkiel Persunay (PT. Jurnal Center Indonesia Publisher, 2026)
Micro-enterprises play a strategic role in the Indonesian economy, particularly in rural areas. However, limited resources and a low level of financial management understanding often lead to operational cost inefficiencies. This study aims to analyze the implementation of a cost control system in improving the efficiency of a micro-enterprise, focusing on a grocery business owned by Mrs. Delin in Tuni Hamlet. The study employs a descriptive qualitative approach using a case study method. Data were collected through in-depth interviews and direct observation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results indicate that the implementation of a simple cost control system through expense recording, budgeting, and expenditure evaluation can improve operational efficiency, as reflected by reduced waste and better cost management. The main challenges in implementing cost control include limited accounting knowledge and informal business management habits. This study is expected to serve as a reference for micro-enterprise owners in improving efficiency through simple and applicable cost control practices.